Topical propranolol for infantile hemangioma: a comprehensive review of mechanisms, clinical efficacy, and novel formulations - Chen, Feifan; Yang, Li; Li, Kunpeng; Chen, Jiajun; Liu, Wenying; Ji, Yi; Xia, Meng; Xie, Jing; Ding, Ke; Zeng, Qiang; Hou, Fang (Frontiers in Pediatrics, 2026)
Infantile hemangioma (IH) is the most common benign soft tissue tumor in children. While most exhibit a tendency for spontaneous regression, a minority can lead to severe, life-threatening complications, necessitating active intervention. Treatment modalities vary depending on the lesion's location, size, and depth. In recent years, topical β-blockers have increasingly become a preferred treatment option for many parents and clinicians. This review aims to systematically summarize the pharmacological mechanisms, clinical efficacy, safety profile, and formulation innovations of topical propranolol in the treatment of IH by synthesizing domestic and international literature, thereby providing a valuable reference for clinical practice and future research.